DOMINASI HABITUS PRAKTIK PEMAKAIAN CADAR SEBAGAI FENOMENA LIVING DI LEMBAGA PESANTREN AN-NUR PUTRI NGRUKEM PENDOWOHARJO SEWON BANTUL YOGYAKARTA (APLIKASI PRAKTIK SOSIAL PIERRE BOUDIEU) - Lailaa Kholily, Aavi (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2024)
Living is a scientific study related to phenomena that occur in society which is based on al-Qur’an and hadith. One example of living phenomena is the wearing of face veils at Islamic boarding school of An-Nur Ngrukem Pendowoharjo, Sewon, Bantul. The unique thing that differentiates the practice of wearing of face veils at the An-Nur Islamic boarding school from others is that the practice of wearing of face veils at An-Nur Islamic boarding school is only done when the female students are studying with one of the teachers at An-Nur. Apart from that, the practice of wearing of face veils at An-Nur Islamic boarding school is not required to wear loose, dark colored clothing like the practice of wearing of face veils in general. This study uses Pierre Bourdiou's sociological approach to analyze this phenomenon. The results of the analysis is that the consistency of the female students in wearing of face veils cannot be separated from the influence of Gus Rum as one of the family's kyai and ustadz who is very pious and respected. Beside that, the students really like his way of teaching, so that even though at first it was not comfortable wearing of face veils, but for the sack of Gus Rum's comfort in teaching, the female students then got used to wearing of face veils and it becomes a custom.